Identification of Novel, Selective Ataxia-Telangiectasia Mutated Kinase Inhibitors with the Ability to Penetrate the Blood-Brain Barrier: The Discovery of AZD1390 - Pike, Kurt G.; Hunt, Thomas A.; Barlaam, Bernard; Benstead, David; Cadogan, Elaine; Chen, Kan; Cook, Calum R.; Colclough, Nicola; Deng, Chao; Durant, Stephen T.; Eatherton, Andrew; Goldberg, Kristin; et al. (Journal of medicinal chemistry, 2024)
The inhibition of ataxia-telangiectasia mutated (ATM) has been shown to chemo- and radio-sensitize human glioma cells in vitro and therefore might provide an exciting new paradigm in the treatment of glioblastoma multiforme (GBM). The effective treatment of GBM will likely require a compound with the potential to efficiently cross the blood-brain barrier (BBB). Starting from clinical candidate AZD0156, 4, we investigated the imidazoquinolin-2-one scaffold with the goal of improving likely CNS exposure in humans. Strategies aimed at reducing hydrogen bonding, basicity, and flexibility of the molecule were explored alongside modulating lipophilicity. These studies identified compound 24 (AZD1390) as an exceptionally potent and selective inhibitor of ATM with a good preclinical pharmacokinetic profile. 24 showed an absence of human transporter efflux in MDCKII-MDR1-BCRP studies (efflux ratio <2), significant BBB penetrance in nonhuman primate PET studies (K-p,K-uu 0.33) and was deemed suitable for development as a clinical candidate to explore the radiosensitizing effects of ATM in intracranial malignancies.